An American Philosophy of Social Security : Evolution and Issues - Brown, J. Douglas (James Douglas), 1898-1986 (Book collections on Project MUSE., 1972)
Is our system of social security, which involves an annual dispersement of thirty billion dollars, as effective and as equitable as it might be? J. Douglas Brown's analysis of the policies of this program and the philosophy on which it was built offers insights into its relation to our social and political systems. He was one of a small number of people who drafted the original Social Security program enacted in 1935. He views a national welfare system as a necessary adjunct to our national system of social insurance (Social Security, Medicare, etc.) and fears that without it the role of so.